Derivative use, ownership structure and lending activities of US banks - Abugri, Benjamin A; Osah, Theophilus Teye (Journal of Economics and Finance, 2021)
Following the 2007–2008 financial crisis, there is widespread interest in understanding how derivative use drives bank lending behavior. Our paper examines the impact of bank ownership structure on the relationship between derivative use and lending activities of U.S. banks. We find that lending recovered faster in larger banks than smaller banks post-crisis and in line with Diamond’s (Diamond DW 1984 Financial intermediation and delegated monitoring. Rev Econ Stud 51:393–414) systemic risk reduction theory, derivative use is positively associated with lending growth. Ownership is significant in explaining the magnitude of the relationship even after controlling for alternative specifications of the derivative use variable. In both normal and crisis periods, the speed of adjustment of lending to derivatives use by stock banks lags that of mutual banks. We suggest that speculative trading in derivatives substitutes for lending growth to a larger extent for stock banks compared to mutual banks. These findings may have important implications for investors and bank regulators. © 2020, Academy of Economics and Finance.
0 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85096023364
Keywords: dept.eco; dept.fin; peer-reviewed